Prevalence of Hepatitis C Viral Infection among Diabetes Mellitus Patients in Qassim Region, Saudi Arabia - Muneerah Hamad Aldubaie; Prarthana M. Suryavamshi; Uma M. Irfan; Hamad A. Al-Hamed; Turki Abdullah Almogbel; Ahmad Almatroudi; Faris Alrumaihi; Khaled Allemailem (Journal of Pure and Applied Microbiology, 2023)
The worldwide prevalence of Diabetes Mellitus (DM) associated with Hepatitis C Virus (HCV) infection are reported with higher rates of morbidity and mortality. The frequency of HCV is approximately 3-4 million cases each year and in parallel the incidence of DM is increasing alarmingly. World Health Organization (WHO) has specified that DM will be the 7th leading cause of mortality by 2030. The increasing association between HCV and DM has been indicated by some significant reports recently. HCV infection leads to hepatic steatosis and rapid insulin resistance, which in turn upsurges the risk factors for hepatic fibrosis and hepatocellular carcinoma. This study is designed to examine the association between HCV and DM, and different risk factors associated with HCV infection in Qassim region, Kingdom of Saudi Arabia (KSA). A total of 634 blood samples were obtained from diabetic and non-diabetic patients. These blood samples were first screened for HCV infection by enzyme-linked immunosorbent assay (ELISA) and positive samples were again confirmed by TaqMan HCV quantitative test and the viral load in different samples was estimated. The HCV prevalence was identified as 2.5% in diabetic patients with a positive association between HCV and DM (RR= 1.24, OR= 1.77) which is not significant statistically. However, the HCV prevalence among diabetic females was significantly different from males (p<0.05). The behavioural factors had no significant impact to acquire HCV infection. This study indicated a positive association between HCV and DM. Gender was an association factor in the HCV and DM status. Further studies with larger sample size is significant to properly assess the temporal relationship between HCV and DM.